PENGARUH KUALITAS PELAYANAN INTI DAN KUALITAS PELAYANAN PERIFERAL TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA LABORATORIUM KLINIK GRHA PRODIA SURABAYA - Andika Satria Bagaskara; Woro Utari (Jurnal Manajerial Bisnis, 2023)
This research aims to describe the quality of core services, the quality of peripheral service satisfaction and customer loyalty in the laboratory of Grha Prodia Surabaya clinic. In addition to testing and analyzing the influence of each of these variables. The results of the research obtained for the influence of each variable include the quality of core service has a significant effect on customer satisfaction, peripheral service quality has a significant effect on customer satisfaction, core service quality has a significant effect on customer loyalty, peripheral service quality does not have a significant influence on customer loyalty, core service quality through customer satisfaction has a significant effect on customer loyalty. Customer loyalty, peripheral service quality through customer satisfaction have a significant effect on customer loyalty, and customer satisfaction has a significant effect on customer loyalty.